Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages NUTRITION THE POSITION IN ENGLAND TO-DAY By G. C. M. M'GONIGLE M.D., D.HY., B.S., D.P.H. Medical Officer of Health, Stockton-on-Tees Author of Poverty and Public Health November 1936 Published by the INDUSTRIAL CHRISTIAN FELLOWSHIP 4 The Sanctuary, Westminster, S.W.1 15X/2/217/2